Review of '' Lord of the Poetry in Abbasia Period'' Book - leila Jamshid (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Review and criticism of studies that deal with the lives of literary figures and their influence on literature as one   of the most important branches of human civilization are of high prominence especially when they play important roles in the advancement of educational goals.Such criticisms regardless of whether they cause adornment and acceptance of such works pave the ways for applied  studies.Among these works, the book of '' Lord of the Poetry in Abbasia Period'' iss a work that the author has attempted by choosing the elect  of Abbasia period poets and their poetic characteristics. Poetry of this period is one of the brightest Arabic literature periods.The present study aims to introduce the position and goal of this book after an introduction about the importance of criticism and analysis of literary books and present its content and structural criticism. Since the author has written this book with the aim of pushing enthusiasts of literature which is consistent with some training techniques, it seems that after removing shortcomings and review of this book, it would have optimal performance as a teaching source in M.A courses